The Irrevocable View of the Phinehasian Covenant in Light of the Davidic Covenant - Tuck Seon Chung (STT Amanat Agung, 2019)
Abstract: One may easily have the impression that the promise of an everlasting covenant with Phinehas in Numbers 25:13 has been reached under the Sinai covenant. On closer examination of the question, however, general agreement in fact counts for little. Rather, most of the questions on this point appear to be still open. This article re-examines the efficacy of the Phinehasian covenant by comparing parallelly with the Davidic covenant as to show that the covenant carries the same weight as the Davidic covenant. This paper emphasis on God’s everlasting covenant with Phinehas is unconditional that should not be taken as a bilateral covenant under the Sinai covenant. Thus, how did Christ Jesus fulfill this Phinehasian covenant as the culmination of the covenant promise is worth for a further investigation. Abstrak: Orang mudah mendapatkan kesan bahwa janji kovenan kekal dengan Pinehas dalam Bilangan 25:13 telah digenapi dalam kerangka kovenan Sinai. Namun, melalui penyelidikan yang lebih mendalam, fakta-fakta yang mendukung ternyata sedikit. Sebaliknya, kebanyakan pertanyaan terhadap titik ini nampak masih terbuka. Artikel ini memeriksa kembali kekuatan kovenan Pinehas dengan cara membandingkannya parallel dengan kovenan Daud. Ia memandang bahwa kovenan kekal Allah dengan Daud adalah tidak bersyarat. Signifikansi dari riset ini adalah menguraikan bahwa kovenan Pinehas akhirnya terealisasi dalam Kristus Yesus sebagai kulminasi dari janji kovenan tersebut.